Calcified neurocysticercosis lesions and antiepileptic drug–resistant epilepsy: A surgically remediable syndrome?. Issue 10 (29th August 2013) - Rathore, Chaturbhuj; Thomas, Bejoy; Kesavadas, Chandrasekharan; Abraham, Mathew; Radhakrishnan, Kurupath
Summary Purpose In contrast to the well‐recognized association between acute symptomatic seizures and neurocysticercosis, the association between antiepileptic drug (AED)–resistant epilepsy and calcified neurocysticercosis lesions (CNLs) is poorly understood. We studied the association between AED‐resistant epilepsy and CNLs, including the feasibility and outcome of resective surgery. Methods From the prospective database maintained at our epilepsy center, we reviewed the data of all patients with AED‐resistant epilepsy who underwent presurgical evaluation from January 2001 to July 2010 and had CNL on imaging. We used clinical, neuroimaging, and interictal, ictal, and intracranial electroencephalography (EEG) findings to determine the association between CNL and epilepsy. Suitable candidates underwent resective surgery. Key Findings Forty‐five patients fulfilled the inclusion criteria. In 17 patients, CNL was proven to be the causative lesion for AED‐resistant epilepsy (group 1); in 18 patients, CNL was associated with unilateral hippocampal sclerosis (HS; group 2); and in 10 patients, CNLs were considered as incidental lesions (group 3). In group 1 patients, CNLs were more common in frontal lobes (12/17), whereas in group 2 patients, CNLs were more commonly located in temporal lobes (11/18; p = 0.002). Group 2 patients were of a younger age at epilepsy onset than those in group 1 (8.9 ± 7.3 vs. 12.6 ± 6.8 years, p = 0.003). Perilesional gliosis was more common among patients in group 1 when compared to group 3 patients (12/17 vs. 1/10; p = 0.006). Fifteen patients underwent resective surgery. Among group 1 patients, four of five became seizure‐free following lesionectomy alone. In group 2, four patients underwent anterior temporal lobectomy (ATL) alone, of whom one became seizure‐free; five underwent ATL combined with removal of CNL (two of them after intracranial EEG and all of them became seizure‐free, whereas one patient underwent lesionectomy alone and did not become seizure‐free. Significance In endemic regions, although rare, CNLs are potential cause for AED‐resistant and surgically remediable epilepsy, as well as dual pathology. Presence of perilesional gliosis contributes to epileptogenicity of these lesions. For those patients with CNL and HS, resection of both lesions favors better chance of seizure‐free outcome.